Two Birds with One Stone: High Efficiency and Low Synthetic Cost for Benzotriazole‐Based Polymer Solar Cells by a Simple Chemical Approach. Issue 39 (3rd September 2020) - Xue, Xiaonan; Zheng, Bing; Zhang, Yu; Zhang, Ming; Wei, Donghui; Liu, Feng; Wan, Meixiu; Liu, Juan; Chen, Guangming; Huo, Lijun
Abstract: Low synthetic cost and high performance are becoming a new challenge in designing polymer donors for large‐scaled polymer solar cells (PSCs) fabrication; however, complicated synthetic routes and high material costs hamper the widespread commercial application of OPVs. Here, a simple and low‐cost chemical steric effect (SE) is introduced to BDT‐based side chains. Through adjusting alkyl side chains, the polymeric crystallinity and miscibility are rebalanced and subsequently the photovoltaic device based on the meta‐positioned alkyl polymer outperforms its para‐positioned counterpart. The champion device based on the polymer with the meta‐positioned side chains affords a PCE of 14.53% without sacrificing its high fill factor of 0.77, which could be attributed to a more balanced charge‐carrier transport ability and optimized morphology. This is the highest PCE value reported in BTZ based polymer donors to date. Thus, it shows that the SE applied in high crystalline polymer could pave an easier and cheaper chemical route to realize the coordination of low‐cost fabrication and high‐performance. Abstract : To generate cost‐efficient and high‐performanced polymers, a simple chemical steric effect (SE) is introduced to benzothiophene (BDT)‐based side chains. The polymeric crystallinity and miscibility are rebalanced and a power conversion efficiency (PCE) of 14.53% is achieved. Thus, the SE applied in crystalline polymer pave an easier and cheaper route to realize the coordination of low‐cost fabrication and high‐performance.